Degradation of polycyclic aromatic hydrocarbons (PAHs) and dibenzofuran by actinomyces strain XKDN12 - Nhã, Nguyễn Đương; Minh, Nghiêm Ngọc; Bảo, Nguyễn Ngọc; Hà, Đặng Thị Cẩm (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 123-132, 2005